CONSTRUCTIVISTIC LEARNING MODEL BASED ON COGNITIVE SCIENCE FOR OPTIMIZING CONCEPTUAL UNDERSTANDING TAWHID AT MADRASAH ALIYAH - Muhammad Iqbal; Basri Basri (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to develop a constructivist learning model based on cognitive science to optimize the understanding of the concept of monotheism in Madrasah Aliyah. Using a mixed method approach with a sequential explanatory design integrated with Research and Development (R&D), the study was conducted in 15 Madrasah Aliyah in Aceh involving 45 aqidah teachers and 450 students. Data collection used a combination of quantitative instruments (concept understanding tests, mental model construction scales, learning observations) and qualitative (in-depth interviews, participatory observations, FGD). The results showed a significant increase in students' understanding of the concept of monotheism (t = 8.42, p < 0.01) with a large effect size (Cohen's d = 0.85). SEM analysis revealed a strong correlation between the quality of the mental model and understanding of the concept (r = 0.82, p < 0.01). The learning model succeeded in improving students' ability to connect the concept of monotheism with the reality of life (from 45% to 85%) and developing a coherent mental model (78% of students). MANOVA showed positive effects on conceptual understanding (F = 24.5), analytical skills (F = 18.7), and practical application (F = 21.3). Path analysis identified significant contributions from peer-learning collaboration (32%), teacher-student interaction (28%), and inclusive learning climate (β = 0.45). The developed model proved effective in facilitating the construction of meaningful understanding and providing a practical framework for the implementation of cognitive science-based learning.